Analisis Pengaruh PDRB, Tingkat Pengangguran dan Indeks Pembangunan Manusia Terhadap Tingkat Kemiskinan Diprovinsi Lampung Tahun 2021-2021 - Taufiq Hidayat; Tria Anisanur; Revan Lesta Mahendra; Muhammad Kurniawan (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This research aims to analyze the relationship between Gross Regional Domestic Product (GRDP), unemployment rate, and Human Development Index (HDI) with the poverty rate in Lampung Province during the 2021-2021 period. The data used is secondary data obtained from various official sources. Statistical analysis methods, including correlation and regression analysis, are used to test the relationship between these variables. The research results show that there is a relationship between GRDP, unemployment rate, HDI, and poverty rate in Lampung Province. The implications of these findings are discussed in the context of economic and social development policy at the regional level.